Nonstandard Computational and Bifurcation Analysis of the Rabies Epidemic Model - Wafa F. Alfwzan; Ali Raza; Nauman Ahmed; Amr Elsonbaty; Muhammad Rafiq; Waleed Adel (Journal of Mathematics)
This paper aims to investigate some new dynamics of a new model describing the rabies virus dynamics, taking into account the effect of proper vaccination. The model’s population is divided into three main compartments, namely, susceptible St, infected It, and recovered Rt individuals. The model is formulated and then the equilibrium points of the model are found. The local and global stabilities of equilibrium points of the proposed model are investigated where conditions of stability are attained in terms of key parameters in the model. Bifurcation analysis is performed for the possible occurrence of codimension-one bifurcations in the model. In addition, bifurcation surfaces are plotted in the space of parameters in the model. For the numerical verification, a nonstandard finite difference method is adapted for solving the model and the accurate results of numerical simulations are depicted to reveal the dynamics of the model. The method provides realistic data for the model and these data can be used to predict the spread of the virus and to provide insight into proper procedures and control measures that can be taken.